Diagnosis and management of opacified silicone intraocular lenses in patients with asteroid hyalosis. Issue 1 (January 2015) - Espandar, Ladan; Mukherjee, Nisha; Werner, Liliana; Mamalis, Nick; Kim, Terry
Abstract : N/A: We analyzed 3 calcified silicone IOLs from 2 patients with a history of asteroid hyalosis. In both cases, posterior capsule opacification had been diagnosed and a laser capsulotomy performed before referral. Subsequently, both IOLs were exchanged with hydrophobic acrylic IOLs that were placed in the sulcus. The IOL exchange was challenging due to the open capsule. Light microscopy demonstrated that the white deposits on the explanted IOLs formed an almost confluent crust in some areas, interspersed with clear areas on the posterior optic surfaces. The findings in our cases and in other reported cases may affect the choice of IOL in the presence of asteroid hyalosis. Also, ophthalmologists may consider deferring laser posterior capsulotomy treatment in a calcified silicone IOL to facilitate an IOL exchange procedure. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.